Liquid Chromatography-Tandem Mass Spectrometry for Analysis of Intestinal Permeability of Loperamide in Physiological Buffer - Rubelt, Miriam S.; Amasheh, Salah; Grobosch, Thomas; Stein, Christoph (PLOS ONE, 2012)
Analysis of in vitro samples with high salt concentrations represents a major challenge for fast and specific quantification with liquid chromatography-tandem mass spectrometry (LC-MS/MS). To investigate the intestinal permeability of opioids in vitro employing the Ussing chamber technique, we developed and validated a fast, sensitive and selective method based on LC–MS/MS for the determination of loperamide in HEPES-buffered Ringer's solution. Chromatographic separation was achieved with an Atlantis dC18 column, 2.1 mm×20 mm, 3 µm particle size and a gradient consisting of methanol/0.1% formic acid and ammonium acetate. The flow rate was 0.7 ml/min, and the total run time was 3 min. For quantification, two mass transitions for loperamide and a deuterated internal standard (methadone-d3) were used. The lower limit of loperamide quantification was 0.2 ng/ml. This new LC-MS/MS method can be used for the detection of loperamide in any experimental setup using HEPES-buffered Ringer's solution as a matrix compound.